Job stress On Traffic Police Work Performance - Maria Benedikta Moi Maku Djawa; M. K. P. Abdi Keraf; Yeni Damayanti (Journal of Health and Behavioral Science, 2022)
Abstract. Performance is the result of work that can be achieved by someone in an organization in accordance with their respective responsibilities in order to achieve goals related to organizational goals. Performance can be said as a result of the efforts of someone who has more abilities in certain situations. The purpose of this study was to determine the relationship between job stress and traffic police work performance. The hypothesis of this research is the existence of Job stress on the work performance of traffic police. The participants in this study were members of the police who served in the traffic unit and amounted to 75 people who were obtained using total sampling. The test in this study uses the Pearson Correlation and is carried out by correlating the score of each item with the total score of each variable indicator. The results of this study indicate that the coefficient of negative value in the correlation coefficient or r obtained is 0.560 and a significant value of p = 0.238 (p > 0.05) meaning that there is a significant relationship between Job stress and work performance or the Job stress variable is negatively correlated with work performance.